Female soccer: Part 2-Training considerations and recommendations. - Turner, E.; Munro, A.; Comfort, P. (Strength and Conditioning Journal, 2013)
Part 1 of this article identified the demands of female soccer and the specific areas of development required to optimize performance and reduce the risk of common injuries. Increases in aerobic capacity, strength, and lower limb control were required to improve performance and reduce the risks of common injuries. The aims of part 2 are to provide examples of evidence-based integrated strategies to address the issues identified in part 1 and to ensure not only enhanced performance but also a reduced incidence of common injuries in female soccer players.